Cytomegalovirus—A Risk Factor for Childhood Hearing Loss: A Systematic Review. Issue 6 (November 2021) - Vos, Bénédicte; Noll, Dorie; Whittingham, JoAnne; Pigeon, Marie; Bagatto, Marlene; Fitzpatrick, Elizabeth M.
Abstract : Objective: Permanent hearing loss is an important public health issue in children with consequences for language, social, and academic functioning. Early hearing detection, intervention, and monitoring are important in mitigating the impact of permanent childhood hearing loss. Congenital cytomegalovirus (CMV) infection is a leading cause of hearing loss. The purpose of this review was to synthesize the evidence on the association between CMV infection and permanent childhood hearing loss. Design: We performed a systematic review and examined scientific literature from the following databases: MEDLINE, Ovid MEDLINE(R) Daily and Ovid MEDLINE(R), Embase, and CINAHL. The primary outcome was permanent bilateral or unilateral hearing loss with congenital onset or onset during childhood (birth to 18 years). The secondary outcome was progressive hearing loss. We included studies reporting data on CMV infection. Randomized controlled trials, quasi-experimental studies, nonrandomized comparative and noncomparative studies, and case series were considered. Data were extracted and the quality of individual studies was assessed with the Qualitative Assessment Tool for Quantitative Studies (McMaster University). The quality and strength of the evidence were graded using the Grading of Recommendations Assessment, Development and Evaluation (GRADE). A narrative synthesis was completed. Results: Sixty-five articles were included in the review. Prevalence of hearing loss at birth was over 33% among symptomatic CMV-infected newborns and less than 15% in asymptomatic infections. This difference in prevalence was maintained during childhood with more than 40% prevalence reported for symptomatic and less than 30% for asymptomatic CMV. Late-onset and progressive hearing loss appear to be characteristic of congenital CMV infections. Definitions of hearing loss, degree of loss, and reporting of laterality varied across studies. All degrees and both bilateral and unilateral loss were reported, regardless of symptomatic and asymptomatic status at birth, and no conclusions about the characteristics of hearing loss could be drawn. Various patterns of hearing loss were reported including stable, progressive, and fluctuating, and improvement in hearing (sometimes to normal hearing) was documented. These changes were reported in children with symptomatic/asymptomatic congenital CMV infection, presenting with congenital/early onset/late-onset hearing loss and in children treated and untreated with antiviral medication. Conclusions: Symptomatic and asymptomatic congenital CMV infection should be considered a risk factor for hearing loss at birth and during childhood and for progressive hearing loss. Therefore, CMV should be included as a risk factor in screening and surveillance programs and be taken into account in clinical follow-up of children with hearing loss. Abstract : Supplemental Digital Content is available in the text.